From preferences to Cobb-Douglas utility - Mark Voorneveld (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
We provide characterizations of preferences representable by a Cobb-Douglas utility function.
Keywords: C60; D01; 330; Preferences; Utility theory; Cobb-Douglas; Präferenztheorie; Nutzentheorie; Cobb-Douglas-Produktionsfunktion; Theorie